2016
DOI: 10.1186/s12896-016-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of dermal fibroblasts and keratinocytes in hydroxyethyl starch–based cryoprotectants

Abstract: BackgroundPreservation of human skin fibroblasts and keratinocytes is essential for the creation of skin tissue banks. For successful cryopreservation of cells, selection of an appropriate cryoprotectant agent (CPA) is imperative. The aim of this study was to identify CPAs that minimize toxic effects and allow for the preservation of human fibroblasts and keratinocytes in suspension and in monolayers.ResultsWe cryopreserved human fibroblasts and keratinocytes with different CPAs and compared them to fresh, unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…In the current study, cell viability was ∼70% after thawing and harvest compared with ∼100% viability of the freshly harvested, continuously cultured cells. These are comparable to experiences in other studies, as are the freezing medium and the freeze-thaw technique used [11][12][13][14]. As such, there is no obvious discrepancy in the technical approaches.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, cell viability was ∼70% after thawing and harvest compared with ∼100% viability of the freshly harvested, continuously cultured cells. These are comparable to experiences in other studies, as are the freezing medium and the freeze-thaw technique used [11][12][13][14]. As such, there is no obvious discrepancy in the technical approaches.…”
Section: Discussionsupporting
confidence: 85%
“…The frozen MSCs, suspended at the desired concentration in a cryopreservation medium suitable for infusion, are then thawed just prior to administration. However, a significant number of the frozen MSCs may undergo apoptosis during the freeze-thaw process, although much subsequent study has attempted to minimize this occurrence with improved freeze-thaw approaches and cryopreservatives [11][12][13][14]. A recent report demonstrated that freshly thawed MSCs were not as effective in in vitro potency assays as continuously cultured MSCs of the same passage number [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the consistency of allo-CE was preserved by being stored in culture medium at 22-24˚C for 20 days [17] or cryopreserved at -80˚C in culture medium containing fetal calf serum and glycerol as a cryoprotectant [6], the cell viability of the keratinocytes was depleted in any case. When cells and tissues are cryopreserved, they are damaged by vitrification, cold shock, osmotic injury, and intracellular ice formation [21,22].…”
Section: Wound Healing In Full-thickness Skin Defect Model Of Diabetimentioning
confidence: 99%
“…B) while the 2D cultured cells were irregularly shaped (Data not shown). Using freshly thawed HaCaT cells to mimic cells freshly isolated from tissues , we determined whether the 3D cultured cells are more similar to cells freshly isolated from tissues than the 2D cultured cells by comparing vimentin expression in 2D and 3D cultured HaCaT cells. Vimentin is a biomarker for mesenchymal and indicates the differences in the composition of cell cytoskeleton and the extracellular matrix (ECM) between 2D and 3D cells .…”
Section: Resultsmentioning
confidence: 99%